Transobturator Tape for the Treatment of Stress Urinary Incontinence in a Small Municipal Hospital-Single Surgeon Experience - Branković, Srbobran; Ignjatovic, Ivan Milic; Jovanovic, Bojan (Acta medicae Medianae, 2021)
The aim of the study is to describe a study of 43 patients operated using a transobturator tape (TOT). A prospective study was performed on forty free patients operated between 2014 and 2020. In all patients diagnosis of stress urinary incontinence (SUI) was based on clinical criteria: positive stress test or positive pad test, confirmed urethral hypermobility (>30 degrees), ultrasound and bladder diary for three days. Cystoscopy is performed in all patients to document satisfactory bladder compliance and capacity, and to exclude ordinary pathology of the bladder. In all patients, TOT was performed. Follow up was performed one month, six months, and 12 months after the surgery. All patients were in generally good preoperative health state-American Society of Anesthesia grading system 42/43 (97.6%) (ASA 1-2). The subjective cure was achieved in 36/43 (83.7%) patients after one year. An objective cure was achieved in 32/43 (74.7%) patients after one year. OAB was present preoperatively in 19/43 (44.1%) patients, and postoperatively in 9/43(20.9%) patients (p<0.02). Postoperative complications were minor (Clavien-Dindo grade ≤2) in 42/43 (97.6%) patients. Transobturator tape can be successfully performed in selected patients in a small municipal hospital.